2015
DOI: 10.1111/iep.12133
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen‐containing bisphosphonate therapy: assessment of the alveolar bone structure in rats – a blind randomized controlled trial

Abstract: This study aimed to assess the effect of zoledronic acid exposure on structures of the alveolar bone of rats. The sample was composed of 42 male Wistar rats. Animals in the T1 and T2 groups received weekly doses of 0.2 mg/kg intraperitoneal zoledronic acid for 3 weeks, while animals in the T3 group received the same treatment for 8 weeks. The control groups C1, C2 and C3 received equivalent doses of saline. The first upper molars of Wistar rats in the C2, T2, C3 and T3 groups were extracted. Cone-beam computer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…We also observed that the experimental group exhibit evident delayed reepithelialization at the fourth week, in contrast with other BRONJ models which showed the same condition but during a longer period of time. ( 2 , 9 , 22 , 23 )…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We also observed that the experimental group exhibit evident delayed reepithelialization at the fourth week, in contrast with other BRONJ models which showed the same condition but during a longer period of time. ( 2 , 9 , 22 , 23 )…”
Section: Discussionmentioning
confidence: 99%
“…The standardized radiological parameters for all study groups were 60-70kV with an exposure time of 0.24 seconds. X-ray images were analyzed according to Pacheco using the IMAGE J software® ( 9 ). All images were converted into an 8-bit data (256 grey levels) generating a scale (0-255) for each image.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in animals have also clarified the relationship between bisphosphonates use and changes in alveolar bone tissue . Factors such as stagnation of osteoclastic activity and angiogenesis, which are fundamental to bone repair, have been observed …”
Section: Introductionmentioning
confidence: 99%
“…8 Studies in animals have also clarified the relationship between bisphosphonates use and changes in alveolar bone tissue. 9 Factors such as stagnation of osteoclastic activity and angiogenesis, which are fundamental to bone repair, have been observed. 10,11 This study aimed to analyse the inflammatory response of alveolar bone after pulp injury in rats submitted to two different regimens of zoledronic acid therapy.…”
mentioning
confidence: 99%